Reduction of Radiation Exposure in Atrioventricular Nodal Reentrant Tachycardia Ablations Using an Electroanatomical Mapping System With Fluoroscopy Integration Module - Blockhaus, Christian; Gülker, Jan-Erik; Bufe, Alexander; Seyfarth, Melchior; Koektuerk, Buelent; Shin, Dong-In (Frontiers in Cardiovascular Medicine, 2021)
Introduction Atrioventricular nodal reentrant tachycardia (AVNRT) is a common supraventricular tachycardia. Current guidelines recommend electrophysiology study (EPS) and ablation, which have been proven to show high success rates with very low complication rates. Usually, ablation of AVNRT is performed conventionally using only fluoroscopy. Electroanatomical mapping systems (EMS) are widely used in complex arrhythmias. One of their advantages is their potential in decreasing the need of fluoroscopy time (FT). In this study we analyzed patients undergoing either conventional AVNRT ablation or by using an EMS with a fluoroscopy integrating system (FIS). Material and Methods We included 119 patients who underwent AVNRT ablation in our study. 89 patients were ablated conventionally using only fluoroscopy, 30 patients were ablated using EMS + FIS. Results We found that the use of EMS+FIS led to a significant reduction of FT (449.90 ±217.21 vs. 136.93 ± 109.28 sec., p<0.001) and dose-area-product (DAP, 268.27 ± 265.20 vs. 41.07 ± 27.89 µGym², p<0.001) without affecting the procedure time (PT, 66.55 ± 13.3 vs. 67.33 ± 13.81 min, p=0.783). Furthermore, we found no significance with regard to complications. Conclusion The use of EMS+FIS is safe and feasible. It leads to a significant reduction of both FT and DAP without affecting PT and safety. Hence, EMS+FIS is beneficial for both the operator and the patients by reducing the radiation exposure.